APB Rembau e-Bulletin 16/2025 - UiTM, Academy of Language Studies (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2025)
Welcome to APB E-Bulletin, compiling all of our interesting endeavors to be shared with the world outside. Much prayer has gone into this issue and we hope that you find it to be aspiring, refreshing and encouring. Our goal is to make documentation of moments an interesting journey as well as to share with our readers new information and knowledge. We are pleased to include a variety of contents in this issue and the future issues.